Tidewater Deposits Of High-Brightness Calcium Carbonate And High CaCO3 Limestone In Southern Southeastern Alaska - David A. Hedderly-Smith (Society for Mining, Metallurgy & Exploration, 2001)
Sealaska Corporation, the Alaska Native Regional Corporation of Southeastern Alaska, was organized under the laws of the state of Alaska pursuant to the federal Alaska Native Claims Settlement Act of 1971. Large areas of Sealaska's 630,000-acre (250,000 hectare [ha]) fee subsurface holdings are underlain by carbonate, and while much of this material is assumed to be common variety limestone and lesser dolomite, at least two areas in the Silurian Heceta Limestone contain high-quality limestone at tidewater. This limestone has many potential commercial uses. On northern Prince of Wales Island, about 90 miles (144 km) north-northwest of Ketchikan, resource development at Sealaska's Calder deposit has established a reserve of 13 mil- lion short tons (st) (12 million metric tonnes [mt]) of carbon- ate rock containing an average of greater than 98 percent CaC03, approximately 0.5 percent MgO, less than 0.5 per- cent Si02, and approximately 0.15 percent Fe203, with insolubles averaging less than 0.5 percent and an average Hunter Brightness of 92.07 for the -150 mesh grind (with a bright- ness cutoff of 90). The deposit is open at depth and to the south. Ultimate reserves will likely be several times those currently established. In 1998, Sealaska began mining the Calder deposit, with about 100,000 st (90,000 mt) produced, and also completed a marine terminal one half-mile (800 m) from the deposit. The terminal can load ships up to 680 feet (200 m) in length at a rate of 2,000 st (1,800 mt) per hour. 0 m) in length at a rate of 2,000 st (1,800 mt) per hour. On Dall Island at Breezy Bay, about 60 miles (100 km) southwest of Ketchikan, Sealaska has identified a limestone reserve in excess of 150 million st (135 million mt) that (based on 18 surface samples distributed evenly over about a section of land) contains about 98 percent CaC03, and less than 0.5 percent MgO, 0.5 percent Si02, and 0.15 percent Fe203. Brightness of the Breezy Bay carbonate is considerably less than at Calder. Five samples of brighter material from Breezy Bay returned brightness analyses in the high 80s and low 90s; average brightness is probably below the mid- 80s. Sealaska has also identified a deposit containing more than 19 million st (17 million mt) of similar rock near View Cove, a few miles south of Breezy Bay.